2017
DOI: 10.3390/s17102181
|View full text |Cite
|
Sign up to set email alerts
|

A New Proxy Measurement Algorithm with Application to the Estimation of Vertical Ground Reaction Forces Using Wearable Sensors

Abstract: Measurement of the ground reaction forces (GRF) during walking is typically limited to laboratory settings, and only short observations using wearable pressure insoles have been reported so far. In this study, a new proxy measurement method is proposed to estimate the vertical component of the GRF (vGRF) from wearable accelerometer signals. The accelerations are used as the proxy variable. An orthogonal forward regression algorithm (OFR) is employed to identify the dynamic relationships between the proxy varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 45 publications
0
52
1
Order By: Relevance
“…In addition, similar relationship was observed between acceleration of thorax and lumbar segment obtained by IMU, and acceleration of the center of mass calculated by AGRF. Although previous studies reported that vertical acceleration correlated with vertical trunk acceleration during gait [40,41], no literature investigated the estimation of AGRF by IMU. By Newtonian equation of motion, GRF expresses gravity and acceleration acting on T 4: Relationship between acceleration of trunk (thorax, lumbar spine) obtained by magnetic inertial measurement unit and acceleration of the center of mass calculated from anterior ground reaction force (AGRF) (mean ± SD).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar relationship was observed between acceleration of thorax and lumbar segment obtained by IMU, and acceleration of the center of mass calculated by AGRF. Although previous studies reported that vertical acceleration correlated with vertical trunk acceleration during gait [40,41], no literature investigated the estimation of AGRF by IMU. By Newtonian equation of motion, GRF expresses gravity and acceleration acting on T 4: Relationship between acceleration of trunk (thorax, lumbar spine) obtained by magnetic inertial measurement unit and acceleration of the center of mass calculated from anterior ground reaction force (AGRF) (mean ± SD).…”
Section: Discussionmentioning
confidence: 99%
“…Guo and colleagues [ 87 ] adopted a different approach to estimate the vertical component of the GRF by using the acceleration, directly measured by wearable IMUs, and used it as a proxy variable. The aim of the study was to find a relationship between the acceleration, used as a proxy variable, and the forces measured by means of pressure insoles without regard to a biomechanical modelling.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study the authors also tested different placements for the measuring IMU on the subjects’ back: L5, C7 and forehead. Data synchronization was obtained by a vertical jump before trials and, since the acquisitions were relatively long, the time series were re-aligned every two minutes [ 87 ]. This proposed approach is in contrast with approaches based on detailed biomechanical models and it is claimed to simplify modelling and data acquisition strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate predictions for new data can be made by learning the relationship between a set of independent variables (e.g., IMU signals) and one or more dependent variables (e.g., KAM) (Lin et al, 2016;Halilaj et al, 2018). Several studies have shown that machine learning techniques, such as artificial neural networks (ANN), are powerful tools to deduce biomechanical variables based on measured accelerations or angular velocities of body segments (Leporace et al, 2015;Guo et al, 2017;Ancillao et al, 2018;Wouda et al, 2018;Stetter et al, 2019). The study by Wouda et al (2018) used an ANN approach to estimate vertical GRFs and sagittal knee kinematics during running, based on three inertial sensors placed at the lower legs and the pelvis.…”
Section: Introductionmentioning
confidence: 99%